2022
DOI: 10.3389/fonc.2022.817737
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PELATON, a Ferroptosis Suppressor and Prognositic Signature for GBM

Abstract: PELATON is a long noncoding RNA also known as long intergenic nonprotein coding RNA 1272 (LINC01272). The known reports showed that PELATON functions as an onco-lncRNA or a suppressor lncRNA by suppressing miRNA in colorectal cancer, gastric cancer and lung cancer. In this study, we first found that PELATON, as an onco-lncRNA, alleviates the ferroptosis driven by mutant p53 and promotes mutant p53-mediated GBM proliferation. We also first confirmed that PELATON is a new ferroptosis suppressor lncRNA that funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Hung et al [76] subsequently verified that it has macrophage and monocyte specificity and can be elevated in levels in unstable atherosclerotic plaques. In recent studies, it was shown to be an iron death suppressor and one of the oncogenes of glioblastoma multiforme (GBM) [77]. Our analysis also demonstrates that PELATON can be an independent prognostic factor for TGCT progression-free interval and is associated with the lymphatic invasion and the first location of TGCT.…”
Section: Discussionsupporting
confidence: 64%
“…Hung et al [76] subsequently verified that it has macrophage and monocyte specificity and can be elevated in levels in unstable atherosclerotic plaques. In recent studies, it was shown to be an iron death suppressor and one of the oncogenes of glioblastoma multiforme (GBM) [77]. Our analysis also demonstrates that PELATON can be an independent prognostic factor for TGCT progression-free interval and is associated with the lymphatic invasion and the first location of TGCT.…”
Section: Discussionsupporting
confidence: 64%
“…Studies on the other lncRNAs also proved their functions in oncogenesis, especially in the ferroptosis process, such as knockdown of lncRNA PELATON enhanced sensitivity to ferroptosis inducers to inhibit cell proliferation and invasion in glioblastoma cells ( Fu et al, 2022 ); LINC02609 was positively correlated with late stage, grade, and distant metastasis in ccRCC ( Su et al, 2021 ), and associated with OS in soft tissue sarcoma ( He et al, 2017 ), what’s more, other similar research also identified LINC02609 as ferroptosis-related lncRNA in kidney carcinoma ( Han et al, 2022 ; Xing et al, 2021 ; Bai et al, 2022 ; Shu et al, 2021 ). Further research on the these lncRNAs, especially how these lncRNAs participate in the process of ferroptosis, can provide new insights for revealing the mechanism of renal cell carcinoma at the molecular level.With the in-depth study of tumor immunology and molecular biology, immunotherapy provides a new perspective for tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is an iron-related cell death mechanism that has recently been the subject of fundamental scientific research and has been shown to affect tumor therapy [35][36][37]. Many investigations have revealed that lncRNA is related to tumor ferroptosis, cancer progression, and tumor drug resistance [38][39][40][41]. Therefore, lncRNA is anticipated to be a treatment target and biomarker for CESC.…”
Section: Discussionmentioning
confidence: 99%